Experiences of patients with hip fractures after discharge from hospital. (July 2022) - Sandberg, Magnus; Ivarsson, Bodil; Johansson, Anders; Hommel, Ami
Abstract: Background: To achieve successful rehabilitation after hip fracture and meet patient needs it is important to listen to how individual patients perceive their situation. Purpose: The aim of this study was to explore how patients with hip fractures experience the time after hospitalization. Methods: A qualitative study was performed, data were analyzed using content analysis and included a total of 14 patients who had undergone surgery for a hip fracture. Results: The result comprised two main themes, In the hands of others, and A new unfamiliar life. These included in total nine categories. Conclusions: Not all patients received adequate pain management or were treated in a professional way by the health system. Interventions targeting an improved care trajectory which include all care providers, the person with the hip fracture and their significant others are needed. Further research is needed to reveal the reasons for uneven/differing care.